Evaluation of Aesthetic Response to Clothing Color Combination: A Behavioral and Electrophysiological Study (Journal of Fiber Bioengineering and Informatics, 2013)
The purpose was to focus on the correlation between color combinations of clothing and aestheticresponses. In this study, four levels of contrasting colors were combined in a two-piece suit as stimuli.Behavioral and electrophysiological data were recorded during the course of aesthetic evaluation. Resultsshowed that the higher the contrast of color, the less attractive the clothing is. The early P200 (P2)components were very remarkable in the frontal, central and parietal areas, and the larger amplitudeswere evoked for less attractive color combinations. The late P300 component plays a critical role inthe decision-making aesthetic affirmation. The findings in the current research implied that the P2 andP300 can be viewed as the landmark components for aesthetic response of clothing colors.